The Effect of Rosa damascena on Children's Enuresis: A Randomized Pilot Study - Anoush Azarfar; Ramin Sargazi; Elham Bakhtiari* (Lorestan University of Medical Sciences, 2023)
Background and Aim: Enuresis is one of the common problems among children. The present pilot study was conducted to investigate the effect of Rosa damascene on nocturnal enuresis in children. Materials and Methods: A randomized pilot study was performed from April 2017 to March 2018. The study participants were 40 children aged between 5-12 years with nocturnal enuresis. They were randomly divided to intervention and control groups using block randomization. The intervention group received R. damascena petals under the brand name Gole-Ghand (Barij- essence, Iran) as 5 cc orally, every 8 hours for one month. The control group received desmopressin as nasal spray (Sina Darou, Iran) 1-2 puffs for one month (maximum 20 mg daily). The primary outcome was complete or partial improvement in enuresis. The secondary outcome was frequency of side effects in patients. Results: Twenty-two out of 39 patients 22 (56.4%) were male and 17 patients (43.6%) were female with the average age of 7.3±1.86 years. There was no noticeable distinction between the groups in age, sex, urbanity, history of treatment, and primary or secondary enuresis (p>0.05). Complete improvement was observed in 14 patients (70%) in the control group. Partial improvement was observed in four patients (20%) in the control group and in six patients (31.5%) in the intervention group (p:0.001). No side effect was reported during the study in the intervention group. Conclusion: Based on the results of this pilot study, the use of R. damascena may lead to partial improvement against enuresis in some children. Further studies are required to evaluate this hypothesis.